COVID-19, school closures, and remote teaching: The response time of Brazilian education systems - Roberta dos Reis Neuhold; Márcio Rogério Olivato Pozzer (Íconos)
With the COVID-19 pandemic, physical distancing strategies entered the list of recommended non-pharmaceutical measures to inhibit the spread of the virus. In educational institutions, these measures resulted in the suspension of face-to-face classes, a process known as school closures. However, states with less capacity to face the consequences of the pandemic ended up transfiguring this transitional measure into a permanent condition, exacerbating existing educational inequalities. This was the case in Brazil, which, during a crisis of the federal pact, triggered fragmented and uncoordinated remote teaching programs. It is precisely to Brazil that this article refers, which characterizes the response time to the closure of schools in the federal education network, in the form of the Federal Institutes of Education, Science and Technology (Institutos Federais de Educação, Ciência e Tecnologia), in comparison with the state network. This is an exploratory and descriptive study that uses quantitative and qualitative methods, based on document analysis. It examines the interval between school closures, the disclosure of a contingency plan, the implementation of remote teaching, and the return to face-to-face activities. It finds that, on average, the Institutes took 114 days to publish a contingency plan, in contrast to 34 days for state networks. The article posits the hypothesis that such differences are related to the autonomy of the Institutes in relation to the federal government and the polarization that resulted from president Bolsonaro’s administration, aggravated by his denialist stance.